THE PROBLEMS OF JAVANESE LANGUAGE PHONOLOGY INTERFERENCE INTO ARABIC LANGUAGE STUDENTS AT IMTAQ SHIGHOR ISY KARIMA KARANGANYAR - Muh Idris (Ta'dibi : Jurnal Manajemen Pendidikan Islam, 2022)
The problem of phonological interference of the mother tongue to a foreign language is a problem that is often encountered by students. The purpose of this study is to identify the different types of phonological interference from Javanese to Arabic in learning speaking skills at I'dad Muallimin Tahfizhul Qur'an (IMTAQ) Shighor Isy Karima Karanganyar, as well as the causes and solutions. The data for this study was collected using a qualitative approach and descriptive method, with observations of students speaking in Arabic, interviews, and documentation that were listened to several times and phonological interference on students noted. The Miles and Huberman approach is used in this study's analysis. The findings of this study found that phonological interference in learning speaking skills at IMTAQ Shighor Isy Karima Karanganyar was imperfect in pronouncing vowels and difficulty distinguishing long and short vowels, as well as phonological interference in consonant sounds found in the letters ب، ت، ث، ج، ح، خ، د، ذ، ر، ز، س، ش، ص، ض، ط، ظ، ع، غ، ق، ك.